Terahertz tunable three-dimensional photonic jets - Behrooz Rezaei; Babak Yahyapour; Arash Darafsheh (Scientific Reports, 2024)
Abstract Highly localized electromagnetic field distributions near the “shadow-side” surface of certain transparent mesoscale bodies illuminated by light waves are called photonic jets. We demonstrated formation of three-dimensional (3D) tunable photonic jets in terahertz regime (terajets, TJs) by dielectric micro-objects -including spheres, cylinders, and cubes-coated with a bulk Dirac semimetal (BDS) layer, under uniform beam illumination. The optical characteristics of the produced TJs can be modulated dynamically through tuning the BDS layer’s index of refraction via changing its Fermi energy. It is demonstrated that the Fermi energy of BDS layer has a significant impact on tuning the optical characteristics of the produced photonic jets for both TE and TM polarizations. A notable polarization dependency of the characteristics of the TJs was also observed. The impact of obliquity of the incident beam was studied as well and it was demonstrated that electromagnetic field distributions corresponding to asymmetric photonic jets can be formed in which the intensity at the focal region is preserved in a wide angular range which could find potential application in scanning devices. It was found that the maximum intensity of the TJ occurs at a non-trivial morphology-dependent source-angle.